>INVERSE OF A FUNCTION

>To find the inverse ( f^-1)(x) of a function f(x); follow the following steps:

Example: Find the inverse of
y = 1-2x
1) Write the original equation.
y = 1-2x
2) Solve it in terms of x.
y = 1 -2x
-2x = -1 + y
x = (1-y)/2
3) Interchange y and x in the result of step 2.
x = (1-y)/2 ==> y = (1-x)/2
4) The inverse function f^-1(x) of f(x) = 1 -2x
is therefore f^-1(x) = (1-x)/2

Leave a Reply

Fill in your details below or click an icon to log in:

WordPress.com Logo

You are commenting using your WordPress.com account. Log Out / Change )

Twitter picture

You are commenting using your Twitter account. Log Out / Change )

Facebook photo

You are commenting using your Facebook account. Log Out / Change )

Google+ photo

You are commenting using your Google+ account. Log Out / Change )

Connecting to %s